2020
DOI: 10.7759/cureus.9448
|View full text |Cite
|
Sign up to set email alerts
|

Predicting COVID-19 Pneumonia Severity on Chest X-ray With Deep Learning

Abstract: The need to streamline patient management for coronavirus disease-19 (COVID-19) has become more pressing than ever. Chest X-rays (CXRs) provide a non-invasive (potentially bedside) tool to monitor the progression of the disease. In this study, we present a severity score prediction model for COVID-19 pneumonia for frontal chest X-ray images. Such a tool can gauge the severity of COVID-19 lung infections (and pneumonia in general) that can be used for escalation or de-escalation of care as well as monitoring tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
259
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(303 citation statements)
references
References 18 publications
7
259
3
2
Order By: Relevance
“…We found that both RALE and AI scores derived from CXRs can predict the need for mechanical ventilation and death in patients with COVID-19 pneumonia. Strong correlation between RALE and AI scores in our study (r 2 = 0.79–0.86) is similar to a recent study from Cohen et al (r 2 = 0.81–0.83) 14 . In a recent study on 697 patients with COVID-19 pneumonia with the same Qure.ai algorithm, the AI score was reported as an independent predictor of patients’ outcome 15 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found that both RALE and AI scores derived from CXRs can predict the need for mechanical ventilation and death in patients with COVID-19 pneumonia. Strong correlation between RALE and AI scores in our study (r 2 = 0.79–0.86) is similar to a recent study from Cohen et al (r 2 = 0.81–0.83) 14 . In a recent study on 697 patients with COVID-19 pneumonia with the same Qure.ai algorithm, the AI score was reported as an independent predictor of patients’ outcome 15 .…”
Section: Discussionsupporting
confidence: 92%
“…In a recent study on 697 patients with COVID-19 pneumonia with the same Qure.ai algorithm, the AI score was reported as an independent predictor of patients’ outcome 15 . Although our results are consistent with recent CXRs studies with both RALE and AI algorithm-generated severity assessment 14 , 16 , there are some notable differences. As opposed to prior studies on baseline CXRs at hospital admission 6 , we assessed the performance of severity assessment on serial CXRs.…”
Section: Discussionsupporting
confidence: 89%
“…The suitability of X-ray and CT imaging for COVID-19 (see Figure 11 ), based on recommendations by WHO, is shown in Table 4 , where we discuss the workflow and the practical implementation. The major studies for automated COVID-19 diagnosis using the AI paradigm with X-rays and CT are [ 193 ] [ 194 ] [ 195 ] [ 21 ] [ 196 ] [ 197 ] [ 198 ] [ 199 ] [ 200 ] [ 201 ] [ 22 ] [ 23 ] [ 202 ] [ 192 ]. Due to their popularity in the scientific community, there are several open-source COVID-19 datasets available for X-ray and CT imaging modalities, such as the one from RSNA ( https://www.rsna.org ).…”
Section: Workflow Considerations For Covid-19 Lung Characterization: mentioning
confidence: 99%
“…A similar approach to the proposed work was presented by Ozturk et al [37] in which they used the Darknet model with pretrained weights from the YOLO system [38], achieving the best results using CXR images until the publication of their article. Other approaches presented by Zhanh et al [39] include the use of a CNN as feature extractor and two different multilayer perceptron (MLP) as anomaly detection and confidence prediction; a DenseNet121 model presented by Cohen et al [40] established a baseline for an early version of the same dataset used in this research.…”
Section: Convolutional Neural Network Pneumonia and Covid-19mentioning
confidence: 99%